Ways to reduce the acrylamide formation in cracker products - M. Vass; T. M Amrein; B. Schönbächler; F. Escher; R. AMADÒ (Czech Journal of Food Sciences, 2004)
The sources of reducing sugars and free asparagine of two different cracker products were identified, and acrylamide formation during baking was measured. The application of an asparaginase decreased the acrylamide content by at least 70% in both products. Replacing ammonium hydrogencarbonate by sodium hydrogencarbonate as baking agent and replacing reducing sugars by sucrose resulted in almost 80% less acrylamide in the wheat cracker. Decreasing free asparagine and reducing sugars in the ingredients and a lower end-temperature during baking lowered the acrylamide content of the potato cracker by about 50%.